2015
DOI: 10.1038/npp.2015.340
|View full text |Cite
|
Sign up to set email alerts
|

Blunted Endogenous Opioid Release Following an Oral Amphetamine Challenge in Pathological Gamblers

Abstract: Pathological gambling is a psychiatric disorder and the first recognized behavioral addiction, with similarities to substance use disorders but without the confounding effects of drug-related brain changes. Pathophysiology within the opioid receptor system is increasingly recognized in substance dependence, with higher mu-opioid receptor (MOR) availability reported in alcohol, cocaine and opiate addiction. Impulsivity, a risk factor across the addictions, has also been found to be associated with higher MOR av… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
38
4

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(49 citation statements)
references
References 49 publications
(73 reference statements)
6
38
4
Order By: Relevance
“…A decreased receptor function associated with a protective effect of ICDs and related behaviors in PD is in accordance with a recent clinical trial suggesting therapeutic efficacy of naltrexone, a mu opioid receptor antagonist, on ICDs in PD. 30 PET studies have shown blunted endogenous opioid release following amphetamine challenge in pathological gamblers 31 and decreased availability of mu opioid receptors in different brain areas in pathological gambling and binge eating. 32 However, the mechanisms by which rs1799971 alters mu opioid receptor function and its potential role in addictive behaviors remain to be fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…A decreased receptor function associated with a protective effect of ICDs and related behaviors in PD is in accordance with a recent clinical trial suggesting therapeutic efficacy of naltrexone, a mu opioid receptor antagonist, on ICDs in PD. 30 PET studies have shown blunted endogenous opioid release following amphetamine challenge in pathological gamblers 31 and decreased availability of mu opioid receptors in different brain areas in pathological gambling and binge eating. 32 However, the mechanisms by which rs1799971 alters mu opioid receptor function and its potential role in addictive behaviors remain to be fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…Decrease in BP ND is often interpreted as evidence of increased concentration of endogenous neurotransmitter, according to the competition principle. This principle has been most robustly established for the dopamine system (Laruelle, ) but has been more recently used also for the µ‐opioid system (Colasanti et al, ; Mick et al, ). Although we found significant correlations between exercise‐induced change in BP ND and change in anticipatory food reward activations, not all subjects demonstrated decreased BP ND consistent with endogenous opioid release; in fact, most subjects showed increased BP ND after exercise.…”
Section: Discussionmentioning
confidence: 99%
“…The impulsivity that seems to characterize addiction may be caused by disruptions within the opioid system. Mouse µ receptor knockout models show remarkably decreased motor impulsivity [29] and higher µ receptor availability has been associated with greater impulsivity [30]. Hence, naltrexone, as µ receptor antagonist, through reducing impulsivity may be effective across a rather broad spectrum of addictions involving both broadly defined behavioral addictions and substance use disorders.…”
Section: Discussionmentioning
confidence: 99%